UNIVERSAL ARCHITECTURE DESIGN OF CULTURAL PARK IN MEDAN CITY - Salsabilah, Salwa (Komunitas Menulis dan Meneliti (Kolibi), 2024)
In today's society, with its hectic activity levels, high life pressure, and increasing levels of stress and boredom, people's need for entertainment has never been more important. People who want to enjoy artistic entertainment and channel their artistic talents come from all walks of life, including those of diverse ages, genders, and physical abilities. However, in reality, many buildings in the arts sector have not provided adequate facilities to serve all groups in Medan City. To overcome this problem, the planning and design of the building can apply an architectural concept that is universal design architecture. The purpose of this planning is to realize the idea of the Department of Education and Culture in the field of architecture by providing facilities for the development of arts and culture. It also aims to meet the community's need for a cultural park as a center for learning and art appreciation. This research applies a qualitative descriptive method and focuses on the Cultural Park center. The result of this research is an emphasis on a number of important aspects in designing a building that is accessible to all.